Keberlanjutan Usahatani Kopi Arabika Pada Lahan Miring Di Kecamatan Pagentan Kabupaten Banjarnegara - Makhmud Riyad; Dyah Ethika Noehdijati; Dwi Nugroho Wibowo (Pascasarjana Universitas Jenderal Soedirman, 2020)
Sloping land in the highlands is dominated by annual crops, especially vegetables. The practice of vegetable cultivation by farmers has not fully paid attention to the principles of conservation so as to accelerate the process of land degradation. Arabica coffee farming is an alternative to seasonal crops on sloping land towards sustainable agriculture. Agroecological coffee farming can increase economic value while maintaining the environment. The development of Arabica coffee farming in Pagentan District, Banjarnegara Regency continues to increase from year to year. The sustainability of Arabica coffee farming is inseparable from the ecological, social and economic dimensions. The sustainability assessment of Arabica coffee farming is based on local characteristics. The sustainability of Arabica coffee farming in Pagentan District is currently in a fairly sustainable status with a sustainability index value of 66.07. The highest value of the sustainability index is the social dimension (74.58), followed by the ecological dimension (69.05) and the economic dimension (54.57).